Personality dysfunction and social functioning in schizophrenia. (10th August 2012) - Newton‐Howes, Giles; Marsh, Reginald
ABSTRACT Aim To determine if personality dysfunction is associated with poorer clinical and social indicators in patients with schizophrenia. Methodology An observational study of patients with schizophrenia in psychiatric care assessed patient satisfaction with care, social functioning and psychopathology. Analysis of the relationship between personality and these three domains quantitatively assessed differences between patients with and without comorbid personality dysfunction. Diagnostic confounding was assessed using partial correlation coefficients. Results Forty‐five patients with schizophrenia were studied. In the schizophrenia group, personality dysfunction correlated with poorer social functioning but not poorer satisfaction with care. Linear regression found that the relationship between poorer social functioning and personality disorder in schizophrenia remained, taking other diagnoses and age into account. Partial correlation coefficients confirmed that this was no related to an overlap between personality and schizophrenia symptoms in this sample. Conclusion Personality dysfunction may negatively influence social functioning in patients with schizophrenia but does not appear to impact on patients' views of the care they receive. This is not due to the potential for diagnostic confounding between schizophrenia and personality disorder. Further research using larger samples is needed to confirm this association. Copyright © 2012 John Wiley & Sons, Ltd.